Thermo-economic optimization of air bottoming cycles - Saghafifar, Mohammad; Poullikkas, Andreas (My University, 2015)
In this work a thermo-economic optimization analysis is performed on two air bottoming cycle (ABC) configurations with and without intercooler in the bottoming cycle. Thermo-economic optimization modeling is developed and the effect of the mass flow rate ratio of bottoming cycle air mass flow rate with respect to the topping cycle air mass flow rate is examined in terms of both ABC plant efficiency and total operation cost.
Keywords: Gas turbine; Thermo-economic optimization; Air bottoming cycle